2022
DOI: 10.1039/d2tc00173j
|View full text |Cite
|
Sign up to set email alerts
|

New insights into structure/optical waveguide behavior relationships in linear bisethynylbenzenes

Abstract: In order to establish a relationship between the structure and the optical waveguiding behavior, two series of linear bisethynylbenzenes combining trifluoromethyl and methoxy groups in the core and external rings were synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
2
2
2
Order By: Relevance
“…These results confirmed that the presence of internal channels located in the direction perpendicular to the longest axis of growth allows the propagation of the light, supporting our previously reported hypothesis [ 34 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results confirmed that the presence of internal channels located in the direction perpendicular to the longest axis of growth allows the propagation of the light, supporting our previously reported hypothesis [ 34 ].…”
Section: Resultssupporting
confidence: 92%
“…We have reported some structural requirements for supramolecular aggregates to behave as optical waveguides, adding a new dimension to the study of organic optical waveguides [ 34 ]. In this sense, the presence of internal channels should favor the propagation of light through the crystal.…”
Section: Resultsmentioning
confidence: 99%
“…3b). The α ′ value is lower than some recently reported in optical waveguiding organic crystals 42–44 and on the order of the best derivatives reported recently by our research group 45 and by others. 46 It is known that the excellent crystallinity improves the exciton-photon coupling and the migration of excitons, favouring the light transmission process.…”
Section: Resultscontrasting
confidence: 63%
“…The calculation of the OLC was carried out through the equation I=I 0 e À αx , where I is the PL intensity in the output, I 0 in the input, x is the propagation distance in the crystal and α the parameter to determinate in μm À 1 (Figure 7b). After conversion α to dB μm À 1 (by using the relation α (dB μm À 1 ) = 4.34 α (μm À 1 )), the value calculated for OLC is 1.13×10 À 2 dB μm À 1 , that is in the order of the best derivatives reported, [38][39][40] corroborating the good efficiency of this optical waveguide.…”
Section: Self-assembling Studiessupporting
confidence: 63%
“…In the present work, based on our previous experience in optical waveguides and OFETs, [14–16] a complete microwave‐assisted synthesis of a D‐π‐D‐A‐D‐π‐D benzothiadiazole derivative was carried out to obtain a multifunctional material, as optical waveguide and semiconductor in OFETs, with potential applicability in novel OFEW devices.…”
Section: Introductionmentioning
confidence: 99%